Managing inventory at GoUNESCO. Issue 2 (17th May 2021) - Chejarla, Kalyana C.; Chatterjee, Sandeep
Abstract : Learning outcomes: This case calls out the following inventory management learning objectives in a project context: to understand the project categories of inventories and their drivers for planning purposes, to learn how to manage different categories of inventory and to learn the importance of effective allocation of inventory at different project locations. Case overview/synopsis: GoUNESCO is a start-up formed with the objective of providing a platform for laypersons to engage with places of heritage value. Among others, one of the key components of this platform is "go heritage runs, " in short GHR. In the past three years, the popularity of runs organized under the brand GHR has been increasing, both in terms of locations and the number of participants in each location in successive years. Inventory planning and management for projects is tricky. Different categories of inventory have different implications of shortages or excesses. The case dwells into inventory planning and management of t-shirts and medals, to drive home this point. Complexity academic level: The case can be positioned in service operations management or supply chain management courses while covering inventory management topics for both Master of Business Administration (MBA) and executive MBA students. Supplementary materials: Teaching Notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 11: Strategy.